2021
DOI: 10.3390/ijerph18147570
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Nordic Walking on Bone Properties in Postmenopausal Women with Pre-Diabetes and Non-Alcohol Fatty Liver Disease

Abstract: This study investigated the impact of Nordic walking on bone properties in postmenopausal women with pre-diabetes and non-alcohol fatty liver disease (NAFLD). A total of 63 eligible women randomly participated in the Nordic walking training (AEx, n = 33), or maintained their daily lifestyle (Con, n = 30) during intervention. Bone mineral content (BMC) and density (BMD) of whole body (WB), total femur (TF), femoral neck (FN), and lumbar spine (L2-4) were assessed by dual-energy X-ray absorptiometry. Serum osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Thus, the predictive factors for fracture risk and osteoporosis have been investigated by many researchers. Low BMD has been reported to be associated with aging, low body weight, physical inactivity, smoking, excessive alcohol consumption, diabetes, dyslipidemia, and pernicious anemia [5][6][7]. In addition, chronic iron-deficiency anemia has been suggested to induce bone resorption and increase the risk of osteoporosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the predictive factors for fracture risk and osteoporosis have been investigated by many researchers. Low BMD has been reported to be associated with aging, low body weight, physical inactivity, smoking, excessive alcohol consumption, diabetes, dyslipidemia, and pernicious anemia [5][6][7]. In addition, chronic iron-deficiency anemia has been suggested to induce bone resorption and increase the risk of osteoporosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these characteristics, any method of controlled exercise can contribute to these objectives (Wang et al, 2023). Walking exercises, water aerobics, sports for the elderly, and home exercise programs (Bergström, Lombardo, & Brinck, 2009;Chow, Harrison, & Notarius, 1987;Du et al, 2021;Iwamoto, Takeda, & Ichimura, 2001;Iwamoto, Takeda, Sato, & Uzawa, 2005;Pernambuco et al, 2013) can be indicated. Additionally, at the initial moment of entering an exercise program, the motivation of these people must also be strongly considered (Wang et al, 2023;Weeks, Purvis, & Beck, 2016), to maintain adherence to a future, longer program.…”
Section: Discussionmentioning
confidence: 99%
“…For the last case of this prescription suggestion, older women with severe osteoporosis who have previous fractures, the recommendations should be for greater patient care. Thus, they should not perform exercises with complex methods that require an advanced degree of mobility and prefer conservative methods, such as resistance training and vibrating platforms (Bergström et al, 2009;Chow et al, 1987;Du et al, 2021;Iwamoto et al, 2001Iwamoto et al, , 2005. In these activities, the control of volume and intensity components should be privileged, associated with exercises in reduced gravity, such as hydrogymnastics (Pernambuco et al, 2013), to protect the joints and, above all, possible recurring fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been found to elicit favorable improvements in knee muscle strength among women with low bone mass [ 33 ]. Furthermore, walking has effectively mitigated bone loss in postmenopausal women with pre-diabetes and non-alcoholic fatty liver disease, thereby reducing the likelihood of developing osteoporosis [ 34 ]. Engaging in walking has been found to potentially mitigate the likelihood of developing osteoporosis, as it has been observed to elevate serum ionized calcium levels while concurrently reducing parathyroid hormone and c-terminal telopeptide of type I collagen levels.…”
Section: Discussionmentioning
confidence: 99%